Quality Challenges in Internet of Things-based Services Implementation: An Exploratory Study - Sidek N.; Ali N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Factor analysis; Information systems; Information use; Internet of things; Quality control; Exploratory studies; Government agencies; Qualitative analysis; Qualitative approach; Quality challenges; Quality factors; Semi structured interviews; Systematic literature review; Network security